Przeszłość jako nauczycielka i żródło nadziei. Wprowadzenie do historiozofii Andrieja Sacharowa - Gołąbek, Bartosz (Studia Rossica Posnaniensia, 2016)
The aim of this paper is to discuss the idea of the past based on Andrei Sakharov's essay titled Progress, Coexistence and Intellectual Freedom edited in 1968. Looking through the Stalinist era in the USSR, Sakharov concludes that without dealing with the Stalinist past, there is no hope of achieving peace, progress and stability in international affairs between the two main Cold War adversaries: USSR and USA.